2023
DOI: 10.1021/acsami.3c05881
|View full text |Cite
|
Sign up to set email alerts
|

Modulating On-Demand Release of Vancomycin from Implant Coatings via Chemical Modification of a Micrococcal Nuclease-Sensitive Oligonucleotide Linker

Abstract: Periprosthetic infections are one of the most serious complications in orthopedic surgeries, and those caused by Staphylococcus aureus (S. aureus) are particularly hard to treat due to their tendency to form biofilms on implants and their notorious ability to invade the surrounding bones. The existing prophylactic local antibiotic deliveries involve excessive drug loading doses that could risk the development of drug resistance strains. Utilizing an oligonucleotide linker sensitive to micrococcal nuclease (MN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 45 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…Upon treating the Ti6Al4V pin surfaces with DopaMA, Oligo 5′-carboxy-mCmGTTmCmG-3′-acrydite was UV-cross-linked with PEGDMA to form a coherent and uniform hydrogel coating around the pin (Scheme B, top row). This Oligo sequence was previously validated for selective cleavage by MN at the T–T phosphodiester linkage, with its 3′-acrydite end responsible for copolymerizing with the hydrogel while the 5′-carboxylate end subsequently conjugating with the amino group of ampicillin. ,, Unincorporated Oligo was thoroughly washed out with sterile DI water, and the UV absorption at 260 nm of the aqueous wash solution after 24 h revealed that ∼90% Oligo effectively incorporated into the hydrogel. Ampicillin was then covalently coupled to the 5′ end of the tethered Oligo via amidation upon EDC/sNHS activation of the 5′-carboxyl end (Scheme B, middle row).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Upon treating the Ti6Al4V pin surfaces with DopaMA, Oligo 5′-carboxy-mCmGTTmCmG-3′-acrydite was UV-cross-linked with PEGDMA to form a coherent and uniform hydrogel coating around the pin (Scheme B, top row). This Oligo sequence was previously validated for selective cleavage by MN at the T–T phosphodiester linkage, with its 3′-acrydite end responsible for copolymerizing with the hydrogel while the 5′-carboxylate end subsequently conjugating with the amino group of ampicillin. ,, Unincorporated Oligo was thoroughly washed out with sterile DI water, and the UV absorption at 260 nm of the aqueous wash solution after 24 h revealed that ∼90% Oligo effectively incorporated into the hydrogel. Ampicillin was then covalently coupled to the 5′ end of the tethered Oligo via amidation upon EDC/sNHS activation of the 5′-carboxyl end (Scheme B, middle row).…”
Section: Resultsmentioning
confidence: 99%
“…A rat femoral canal infection model was used to evaluate the ability of the Oligo-Amp hydrogel coated Ti6Al4V IM pins (Ti-Oligo-Amp + S. aureus) to prevent S.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations